Cultivation technology of the winter soft wheat variety “Aksiniya” in the southern part of the Rostov region - A. V. Alabushev; A. S. Popov; D. M. Marchenko; G. V. Ovsyannikova; A. A. Sukharev (Зерновое хозяйство России)
The article presents the results of three-year study (2015–2017) of the effect of various cultivation technologies on the productivity of winter soft wheat variety “Aksiniya”. The study was carried out on blackearth (chernozem) soils of the southern part of the Rostov region, in the fields of the FSBSI “Agricultural Research Center “Donskoy”. There was studied an effect of the sowing time after different forecrops on the variety resistance to lodging. There was identified high variety resistance to lodging in all variants of the experiment. There was described a change in the dynamics of the “Aksiniya” productivity depending on the sowing period after different forecrops. There was a positive reaction of the variety for an early planting on 10th September. During sowing on 10th September, the yield was 5.26–6.81 t/ha, depending on the forecrops. At sowing in later terms there is a tendency to yield decrease. In 2015–2017 the winter soft wheat variety “Aksiniya” sown in fallow land or after peas formed the products of the 2nd class, when sown after sunflower the variety formed the product of the 3d class on average. The calculation of production profitability has shown that the most effective forecrop for the winter soft wheat variety “Aksiniya” is pea. Low production costs for the forecrop peas ensured the production profitability of 165.6–204.5%, depending on the sowing period. The minimum production profitability of the variety sown after sunflower was 83.9–111.4% depending on the sowing period. It has been established that the winter soft wheat variety “Aksiniya” forms the yield due to the number of ears per area unit and due to the ear productivity. Therefore, when cultivating it is necessary to pay special attention to early nitrogen fertilizing, or to apply ammonium sulfate in a dose of N30 before sowing, which will provide a conditional net income of up to 58 363 rubles per hectare, and will increase profitability up to 233%.